Temporal and tissue-specific regulation of a Brassica napus stearoyl-acyl carrier protein desaturase gene. - Slocombe, S; Piffanelli, P; Fairbairn, D; Bowra, S; Hatzopoulos, P; Tsiantis, M; Murphy, D (1994)
The nucleotide sequence of a Brassica napus stearoyl-acyl carrier protein desaturase gene (Bn10) is presented. This gene is one member of a family of four closely related genes expressed in oilseed rape. The expression of the promoter of this gene in transgenic tobacco was found to be temporally regulated in the developing seed tissues. However, the promoter was also particularly active in other oleogenic tissues such as the tapetum and pollen grains. This raises the interesting question of whether seed-expressed lipid synthesis genes are regulated by separate tissue-specific determinants or by a single factor common to all oleogenic tissues. Parts of the plants undergoing rapid development such as the components of immature flowers and seedlings also exhibited high levels of promoter activity. These tissues are likely to have an elevated requirement for membrane lipid synthesis. Stearoyl-acyl carrier protein desaturase transcript levels have previously been shown to be temporally regulated in the B. napus embryo (S.P. Slocombe, I. Cummins, R.P. Jarvis, D.J. Murphy [1992] Plant Mol Biol 20: 151-155). Evidence is presented demonstrating the induction of desaturase mRNA by abscisic acid in the embryo.